2021
DOI: 10.31486/toj.21.0031
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Platelet-Rich Plasma on Symptom Reduction in Patellar Tendinopathy

Abstract: A 19-year-old Division-1 collegiate soccer player presents to the training room with insidious onset right anterior knee pain. The pain started while she was doing rehabilitation following a right anterior cruciate ligament (ACL) reconstruction using a contralateral patellar tendon autograft. She has point tenderness over her right medial proximal patellar tendon, and she describes pain that worsens with repetitive loading of her knee during activities such as squats and running. She is diagnosed with patellar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Of note, critical factors influencing the efficacy of PRP treatments include the preparation method and disease stage. Although animal model studies have suggested that LR-PRP may yield a higher regenerative capacity for tendon healing at an earlier stage compared with LP-PRP, human clinical investigations have not demonstrated similar findings [35][36][37][38][39] . Thus, LR-PRP may represent a more robust treatment modality for patellar tendinopathy; however, use of either formulation is likely acceptable.…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…Of note, critical factors influencing the efficacy of PRP treatments include the preparation method and disease stage. Although animal model studies have suggested that LR-PRP may yield a higher regenerative capacity for tendon healing at an earlier stage compared with LP-PRP, human clinical investigations have not demonstrated similar findings [35][36][37][38][39] . Thus, LR-PRP may represent a more robust treatment modality for patellar tendinopathy; however, use of either formulation is likely acceptable.…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…More than 50% of all shoulder pain cases are considered to be related to tendinopathies of the rotator cuff (RC), such as tendinosis and incomplete thickness tears of the supraspinatus [ 81 ]. In the management of RC tendinopathy, physical rehabilitation, rest, and nonsteroidal anti-inflammatory drugs are considered conventional treatments; however, the best treatment is still inconclusive [ 83 , 84 ].…”
Section: Rotator Cuff Tendinopathymentioning
confidence: 99%